At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To rewrite the equation [tex]\( f(x) = (3x - 9)(x + 1) \)[/tex] in vertex form by completing the square, follow these steps:
1. Expand the equation:
[tex]\[ f(x) = (3x - 9)(x + 1) \][/tex]
Distribute the terms:
[tex]\[ f(x) = 3x(x + 1) - 9(x + 1) \][/tex]
[tex]\[ f(x) = 3x^2 + 3x - 9x - 9 \][/tex]
Combine like terms:
[tex]\[ f(x) = 3x^2 - 6x - 9 \][/tex]
2. Rewrite the quadratic in the form [tex]\( ax^2 + bx + c \)[/tex]:
[tex]\[ f(x) = 3x^2 - 6x - 9 \][/tex]
3. Complete the square:
- Factor out the coefficient of [tex]\( x^2 \)[/tex] (which is 3) from the first two terms:
[tex]\[ f(x) = 3(x^2 - 2x) - 9 \][/tex]
- To complete the square inside the parentheses, take half the coefficient of [tex]\( x \)[/tex] (which is [tex]\(-2\)[/tex]), square it, and add and subtract this square inside the parentheses. Half of [tex]\(-2\)[/tex] is [tex]\(-1\)[/tex], and [tex]\((-1)^2\)[/tex] is 1:
[tex]\[ f(x) = 3(x^2 - 2x + 1 - 1) - 9 \][/tex]
- Simplify the terms inside the parentheses:
[tex]\[ f(x) = 3((x - 1)^2 - 1) - 9 \][/tex]
- Distribute the 3:
[tex]\[ f(x) = 3(x - 1)^2 - 3 - 9 \][/tex]
- Combine constants:
[tex]\[ f(x) = 3(x - 1)^2 - 12 \][/tex]
So, the equation in vertex form is:
[tex]\[ f(x) = 3(x - 1)^2 - 12 \][/tex]
1. Expand the equation:
[tex]\[ f(x) = (3x - 9)(x + 1) \][/tex]
Distribute the terms:
[tex]\[ f(x) = 3x(x + 1) - 9(x + 1) \][/tex]
[tex]\[ f(x) = 3x^2 + 3x - 9x - 9 \][/tex]
Combine like terms:
[tex]\[ f(x) = 3x^2 - 6x - 9 \][/tex]
2. Rewrite the quadratic in the form [tex]\( ax^2 + bx + c \)[/tex]:
[tex]\[ f(x) = 3x^2 - 6x - 9 \][/tex]
3. Complete the square:
- Factor out the coefficient of [tex]\( x^2 \)[/tex] (which is 3) from the first two terms:
[tex]\[ f(x) = 3(x^2 - 2x) - 9 \][/tex]
- To complete the square inside the parentheses, take half the coefficient of [tex]\( x \)[/tex] (which is [tex]\(-2\)[/tex]), square it, and add and subtract this square inside the parentheses. Half of [tex]\(-2\)[/tex] is [tex]\(-1\)[/tex], and [tex]\((-1)^2\)[/tex] is 1:
[tex]\[ f(x) = 3(x^2 - 2x + 1 - 1) - 9 \][/tex]
- Simplify the terms inside the parentheses:
[tex]\[ f(x) = 3((x - 1)^2 - 1) - 9 \][/tex]
- Distribute the 3:
[tex]\[ f(x) = 3(x - 1)^2 - 3 - 9 \][/tex]
- Combine constants:
[tex]\[ f(x) = 3(x - 1)^2 - 12 \][/tex]
So, the equation in vertex form is:
[tex]\[ f(x) = 3(x - 1)^2 - 12 \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.